SUSTAINABLE EGG SUPPLY CHAIN MODEL WITH GREEN SUPPLY CHAIN MANAGEMENT APPROACH - Kimberly Febrina Kodrata; Hasan Sitorus (Bulletin of Engineering Science, Technology and Industry, 2025)
This research aims to develop a sustainable egg supply chain model through the application of Green Supply Chain Management (GSCM). The research method used is qualitative with a literature study approach, through analysis of various relevant national and international journals. The results of the study show that the main dimensions of GSCM that affect the sustainability of the egg supply chain include green purchasing, green manufacturing, green distribution, reverse logistics, and green collaboration. The application of this concept is able to reduce production waste, reduce carbon emissions, increase cost efficiency, and strengthen the competitiveness of egg products in the market. The resulting conceptual model describes a circular supply chain system, where waste and production by-products can be reused as new inputs in the production process. Thus, GSCM is not only oriented towards economic efficiency, but also supports environmental and social sustainability in an integrated manner. This study recommends the importance of collaboration between farmers, distributors, and the government in strengthening the implementation of green supply chains in the egg agribusiness sector.